2016
DOI: 10.1136/archdischild-2016-311043
|View full text |Cite
|
Sign up to set email alerts
|

Tidal volume delivery during continuous chest compressions and sustained inflation

Abstract: Chest recoil generates V depending on an adequate distending pressure. This has previously been demonstrated in adult animals. A pressure of ∼25 cm HO is needed to achieve an adequate V delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…Solevåg et al reported the need for a PIP of approximately 25 cmH 2 O to achieve adequate V T in piglet cadavers and determined distending pressure during CC+SI [28]. This study suggests that chest recoil produces an inflation pressuredependent V T allowing passive ventilation during CCs [28]. A similar observation was reported during chest recoil after the application of a downward force on the chest of infants undergoing surgery requiring general anesthesia [29].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Solevåg et al reported the need for a PIP of approximately 25 cmH 2 O to achieve adequate V T in piglet cadavers and determined distending pressure during CC+SI [28]. This study suggests that chest recoil produces an inflation pressuredependent V T allowing passive ventilation during CCs [28]. A similar observation was reported during chest recoil after the application of a downward force on the chest of infants undergoing surgery requiring general anesthesia [29].…”
Section: Discussionsupporting
confidence: 66%
“…Although there is sufficient evidence that an inflation pressure of 20 to 25 cmH 2 O delivers a high V T in preterm infants [13,14], no study has ever measured the optimal PIP and the delivery of adequate V T during CC in the delivery room. Solevåg et al reported the need for a PIP of approximately 25 cmH 2 O to achieve adequate V T in piglet cadavers and determined distending pressure during CC+SI [28]. This study suggests that chest recoil produces an inflation pressuredependent V T allowing passive ventilation during CCs [28].…”
Section: Discussionmentioning
confidence: 69%
“…During compression of the chest, volume is exhaled and during chest recoil, gas passively flows back into the lungs. The required distending pressure to achieve passive lung ventilation and adequate tidal volume delivery is ~25cmH2O, which correlated in cadaver piglets (r=0.83, p<0.001), manikins (r=0.98, p<0.001), and when combined (piglets + manikins) (r=0.49, p<0.001) 48 . A similar observation was reported during chest recoil after a downward force was applied to the chest of infants undergoing surgery requiring general anesthesia 49 .…”
Section: Chest Compression and Sustained Inflationmentioning
confidence: 94%
“…Li et al reported that surviving piglets had significantly higher values of ETCO 2 , VCO 2 , and PECO 2 during CPR compared to non-surviving piglets, suggesting that continuously monitoring ETCO 2 , VCO 2 , and PECO 2 during CC has the potential to be a non-invasive method to indicate ROSC [40]. To further investigate if other parameters could be used as early outcome predictors after CPR, Solevåg et al examined if cerebral and renal tissue oxygen saturation was different between surviving piglets and non-surviving piglets that were resuscitated after asphyxiainduced cardiac arrest [41]. The relationship of the tissue oxygen saturations with cardiac output, blood pressure, and biochemical variables was also examined [41].…”
Section: Respiratory Parametersmentioning
confidence: 99%
“…To further investigate if other parameters could be used as early outcome predictors after CPR, Solevåg et al examined if cerebral and renal tissue oxygen saturation was different between surviving piglets and non-surviving piglets that were resuscitated after asphyxiainduced cardiac arrest [41]. The relationship of the tissue oxygen saturations with cardiac output, blood pressure, and biochemical variables was also examined [41]. No correlation between cardiac output or blood pressure and cerebral or renal tissue oxygen saturation was observed.…”
Section: Respiratory Parametersmentioning
confidence: 99%